THE EFFECT OF HEALTH PROMOTION USING AUDIO-VISUAL MEDIA ON HAND WASHING IMPLEMENTATION IN KINDERGARTEN STUDENTS GALILEA HOSANNA KIDS MEDAN, 2023 - Simanjuntak, Vitalia Hanako Murni (Pendidikan Bahasa Indonesia dan Sastra (PENDISTRA), 2022)
Washing hands with soap is cleaning hands using soap and water properly to avoid the spread of disease. Pre-school children are susceptible to health diseases, one of which is due to lack of hand washing. Audio visual media is one of the media that can be used for learning to wash hands. The purpose of this study was to analyze the effect of providing education with audiovisual media on correct hand washing behavior in pre-school age children. The research design is a one group pre test post test design. The population of this study was all students in Galilea Hosanna Kids Medan Kindergarten as many as 35 students with a total sampling technique. The independent variable is the audio visual media of hand washing and the dependent variable is the good and right hand washing behavior. Collecting data using a check list sheet according to the SOP for hand washing and observation. Data collection techniques using editing, coding, scoring, tabulating, and statistical tests using the Wilcoxon Signed Rank Test. The results of the study from 35 respondents, before being shown the audio- visual media, most of the respondents were less capable of 25children (71.4%), after being shown the audio-visual media, most of the respondents had good abilities, a total of 22 children (62.9%) . Wilcoxon statistical test shows p value =0.000 < a (0.05) so that H0 is rejected or H1 is accepted. It is recommended that the provision of health education to preschool-age children use audiovisual media as an effort to increase children's compliance.